Integration of Montessori Approach with Tilawati and Ummi Methods for Children's Al-Qur'an Literacy - Syarifah, Himatus; Suparto, Suparto (Maharot : Journal of Islamic Education, 2025)
Qur'anic literacy skills in early childhood are an important foundation in Islamic education. However, the learning methods used are often conventional and less adaptive to the psychological development and learning needs of today's children, especially in urban environments. This study is aims to answer this need by analyzing the potential integration between the Montessori approach and popular Qur'anic learning methods in Indonesia, namely Tilawati and Ummi. This study uses a qualitative approach based on literature study, by examining various scientific sources related to Montessori pedagogical principles, characteristics of the Tilawati and Ummi methods, and the concept of children's Qur'anic literacy. The results of the study show that there are important common points between the three approaches, such as gradual learning, strengthening affection, and orientation to child development. The Montessori approach provides strength in the multisensory aspects and learning independence, while Tilawati and Ummi provide systematic reading and spiritual habituation. The integration of the three offers a more contextual, fun, and spiritual model of children's Qur'an literacy learning. This study makes a conceptual contribution to the development of early childhood Islamic education curriculum and opens space for the development of more adaptive learning models in the future.